Planting gardens to support insect pollinators. Issue 1 (20th February 2019) - Majewska, Ania A.; Altizer, Sonia
Abstract: Global insect pollinator declines have prompted habitat restoration efforts, including pollinator‐friendly gardening. Gardens can provide nectar and pollen for adult insects and offer reproductive resources, such as nesting sites and caterpillar host plants. We conducted a review and meta‐analysis to examine how decisions made by gardeners on plant selection and garden maintenance influence pollinator survival, abundance, and diversity. We also considered characteristics of surrounding landscapes and the impacts of pollinator natural enemies. Our results indicated that pollinators responded positively to high plant species diversity, woody vegetation, garden size, and sun exposure and negatively to the separation of garden habitats from natural sites. Within‐garden features more strongly influenced pollinators than surrounding landscape factors. Growing interest in gardening for pollinators highlights the need to better understand how gardens contribute to pollinator conservation and how some garden characteristics can enhance the attractiveness and usefulness of gardens to pollinators. Further studies examining pollinator reproduction, resource acquisition, and natural enemies in gardens and comparing gardens with other restoration efforts and to natural habitats are needed to increase the value of human‐made habitats for pollinators. Abstract : Article Impact Statement : Gardens with high plant species diversity and sun exposure, more woody vegetation, and larger size benefit pollinators. Abstract : Siembra jardines para dar soporte a los insectos polinizadores Resumen: La declinación mundial de insectos polinizadores ha dado pie a esfuerzos de restauración, incluyendo la jardinería amigable con los polinizadores. Los jardines pueden proporcionar néctar y polen para los insectos adultos y también pueden ofrecer recursos reproductivos, como sitios de anidación y plantas hospederas para las orugas. Realizamos una revisión y un meta‐análisis para examinar cómo las decisiones que toman los jardineros relacionadas a la selección de plantas y el mantenimiento del jardín influyen se la supervivencia, abundancia y diversidad de los polinizadores. También consideramos las características de los paisajes vecinos y los impactos de los enemigos naturales de los polinizadores. Nuestros resultados indicaron que los polinizadores respondieron positivamente a la alta diversidad de especies de plantas, la vegetación leñosa, el tamaño del jardín y la exposición al sol, mientras que respondieron negativamente a la separación entre los jardines y los sitios naturales. Las características intrínsecas de los jardines tuvieron una mayor influencia sobre los polinizadores que los factores del paisaje vecino. El creciente interés por la jardinería para polinizadores resalta la necesidad de entender como los jardines contribuyen a la conservación y como algunas características de los jardines pueden incrementar lo útil y atractivo de los jardines para los polinizadores. Se requieren estudios más profundos que examinen la reproducción de los polinizadores, la adquisición de recursos y los enemigos naturales en los jardines, y también que comparen a los jardines con otros esfuerzos de restauración y con los hábitats naturales para incrementar el valor de los hábitats para polinizadores creados por humanos. 摘要: 为应对全球昆虫传粉者的减少, 人们发起了生境恢复工作, 如培植传粉者友好的花园。花园不仅为成体昆虫提供了花蜜和花粉, 还能提供繁殖资源, 如筑巢地和毛虫的寄主植物 。 我 们通过文献综述和荟萃分析, 研究了花园管理者在植物选择和花园维护方面的决策如何影响传粉者的生存、丰度及多样性, 并将周围景观特征及传粉者天敌的影响纳入考虑。结果表明, 较高的植物物种多样性、木本植被覆盖、较大的花园面积和阳光照射对传粉者有积极作用, 而花园生境与自然环境的分隔则对传粉者有负面影响。花园内部特征比周围景观因素对传粉者的影响更大。人们对为传粉者建造花园的日益浓厚的兴趣, 突显了我们需要更好地理解花园如何促进对传粉者的保护以及花园的一些特征如何提高其对传粉者的吸引力和有用性。未来仍需进一步研究传粉者在花园中的繁殖情况、资源需求及其天敌的影响, 并将花园与自然生境和其它恢复项目比较, 以提升传粉者的人工生境的价值。【翻译: 胡怡思; 审校: 聂永刚】